2011
DOI: 10.3176/eng.2011.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of surface roughness parameters achieved by hard turning with the use of PCBN tools

Abstract: The turning of hardened steels has been applied in many cases in production. Currently, the most important problem is concerned with the properties of the surface finish. This paper investigates the effect on surface finish in a continuous dry turning of hardened steel when using polycrystalline cubic boron nitride tools. The surface profiles (2D arrangement) and surface topography (3D arrangement), generated during the hard turning operation on an EN 41Cr4 low chromium alloy steel, heat treated to the hardnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…In recent past people associated with industrial production and scientific research have shown increasing interest in hard turning of steel since the process possesses a number of potential advantages, including lower equipment costs, shorter setup time, high accuracy, fewer process steps, greater part geometry flexibility, and usually there is no need to use cutting fluid during turning of hard steel. According to one estimate, use of hard turning in the manufacturing of complex parts could reduce manufacturing costs by up to 30 times [1,2] It has been reported that hard turning processes provide high level of accuracy in terms of the form and size, high quality of surface finish and surface integrity (SI) in workpieces [3]. SI generated in the part by a machining operation constitutes several factors such as roughness, hardness, residual stresses, micro-structural changes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In recent past people associated with industrial production and scientific research have shown increasing interest in hard turning of steel since the process possesses a number of potential advantages, including lower equipment costs, shorter setup time, high accuracy, fewer process steps, greater part geometry flexibility, and usually there is no need to use cutting fluid during turning of hard steel. According to one estimate, use of hard turning in the manufacturing of complex parts could reduce manufacturing costs by up to 30 times [1,2] It has been reported that hard turning processes provide high level of accuracy in terms of the form and size, high quality of surface finish and surface integrity (SI) in workpieces [3]. SI generated in the part by a machining operation constitutes several factors such as roughness, hardness, residual stresses, micro-structural changes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Hard turning avoids the use of subsequent finishing processes as this process is characterized by a high level of accuracy in terms of the form and size, high quality of surface finish and surface integrity (SI ) in workpieces [3][4][5]. The establishment of adequate machining guidelines requires the study of several factors (roughness, hardness, residual stresses, micro-structural changes, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The type of wear depends upon the continuity or interruption of the tool-workpiece contact as well as on the CBN percentage in the PCBN composite: abrasive wear has been found in continuous cutting conditions, while chipping was found as an addition to abrasion in the interrupted cutting [1], [9], [25]. Although there is a body of literature reporting on the performance of both low and high-CBN grades in conventional machining, no studies have addressed wear/cutting performance of these materials micro-textured in such a way that they can be employed in grinding-type operations.…”
Section: Introductionmentioning
confidence: 99%
“…Laser ablation technology has been successfully used for the production of macro-features/edges for cutting inserts on ultra-hard materials with a variety of rake and clearance angles. The variation of the geometrical characteristics of the macro-cutting edges has been reported in literature: negative rake angles in the range -6°/-10° are typically utilised for Journal of Manufacturing Science and Engineering, Transactions of the ASME 5 PCBN composites [9]- [12] while rake angles of circa 0° have been used especially for single crystal diamond [13], [14]. While laser ablation has been widely employed for straight and profiled cutting of diamond [10], [11], there have not been many studies for generating geometrically controlled micro-features on flat and curved diamond surfaces until recently [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation